Impact of Smoking, Obesity and Maternal Diabetes on SHBG Levels in Newborns - Aydin, Banu Kucukemre; Yasa, Beril; Moore, Joseph P.; Yasa, Cenk; Poyrazoglu, Sukran; Bas, Firdevs; Coban, Asuman; Darendeliler, Feyza; Winters, Stephen J. (Experimental and Clinical Endocrinology & Diabetes, 2021)
Background Low levels of SHBG have become a marker for insulin resistance and diabetes. Babies born to mothers who are obese, have diabetes, or smoke during pregnancy are at greater risk of developing obesity and diabetes later in life.Aims To examine the impact of maternal obesity, diabetes and smoking on SHBG levels in newborns.Study design This cross-sectional study is part of an ongoing multicenter, longitudinal study.Subjects 98 healthy newborns and their parents, including 16 mothers with diabetes and 31 mothers with a smoking history.Outcome measures Cord blood and second day venipuncture samples were collected for measurement of SHBG and insulin.Results Babies born to mothers with diabetes had lower SHBG levels in cord blood [14.0 (8.9–20.4) vs. 19.6 (14.9–25.1) nmol/L; p=0.011] and on day 2 [18.8 (12.6–21.2) vs. 22.9 (17.1–29.1) nmol/L; p=0.015] than controls. Maternal diabetes remained negatively associated with SHBG levels in cord blood (p=0.02) and on day 2 (p=0.04) when adjusted for mothers’ age, smoking status, pre-pregnancy weight and weight gain during pregnancy. SHBG levels in cord blood and day 2 samples were similar in babies born to mothers who were overweight-obese but not diabetic vs. normal weight, or were smokers when compared to non-smokers.Conclusions: SHBG levels are lower in newborns born to mothers with diabetes than without diabetes, and may be a marker for babies’ life-long risk for abnormal metabolic health. On the other hand, the adverse effects of tobacco smoke on the fetus do not appear to directly influence SHBG levels.
Keywords: obesity; diabetes; metabolic syndrome; SHBG; smoking.